2014
DOI: 10.1039/c3cc47777k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced noble gas adsorption in Ag@MOF-74Ni

Abstract: Various amounts of Ag nanoparticles were successfully deposited in porous MOF-74Ni (or Ni/DOBDC) by an auto-reduction method. An optimized silver-loaded MOF-74Ni was shown to have an improved Xe adsorption capacity (15% more) at STP compared to the MOF without silver nanoparticles. The silver-loaded sample also has a higher Xe/Kr selectivity. These results are explained by the stronger interactions between polarizable Xe molecules and the well-dispersed Ag nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 41 publications
4
133
2
Order By: Relevance
“…8 As expected from the nature of isotherms, a greater Q st for Xe (29 kJ/mol) than for Kr (22 kJ/mol) was calculated for Co 3 (HCOO) 6 , and similar Q st trends were also observed for the other isostructural metal analogues ( Figure 5). The follow-up breakthrough experiments backed up the Xe selectivity (∼6) for the M 3 (HCOO) 6 series. 8 Simulations showed that each Xe atom optimally fits within a segment (i.e., a zig or a zag) and thus can interact more effectively with the π cloud of the formate groups on the pore surface.…”
Section: (Hcoo)supporting
confidence: 78%
See 4 more Smart Citations
“…8 As expected from the nature of isotherms, a greater Q st for Xe (29 kJ/mol) than for Kr (22 kJ/mol) was calculated for Co 3 (HCOO) 6 , and similar Q st trends were also observed for the other isostructural metal analogues ( Figure 5). The follow-up breakthrough experiments backed up the Xe selectivity (∼6) for the M 3 (HCOO) 6 series. 8 Simulations showed that each Xe atom optimally fits within a segment (i.e., a zig or a zag) and thus can interact more effectively with the π cloud of the formate groups on the pore surface.…”
Section: (Hcoo)supporting
confidence: 78%
“…8,11 The adsorption of Xe in nanoporous Co 3 (HCOO) 6 shows a type I adsorption isotherm (26 wt % at 25°C and 100 kPa), while the adsorption isotherm for Kr was found to be linear. 8 As expected from the nature of isotherms, a greater Q st for Xe (29 kJ/mol) than for Kr (22 kJ/mol) was calculated for Co 3 (HCOO) 6 , and similar Q st trends were also observed for the other isostructural metal analogues ( Figure 5). The follow-up breakthrough experiments backed up the Xe selectivity (∼6) for the M 3 (HCOO) 6 series.…”
Section: (Hcoo)mentioning
confidence: 99%
See 3 more Smart Citations